Turning crisis into opportunities: how teachers exercise agency during school closures - J. MacLean; A. Hibert; N. Pantić; M. Phillips; D. Gašević; Y-S. Tsai (Social Sciences and Humanities Open)
This study explored how practising and pre-service teachers exercised their individual and collective agency in response to the school closures in Scotland and Australia during the COVID-19 pandemic. Seven practising and nine pre-service teachers completed an online log and participated in interviews on the challenges they faced working individually and collectively during COVID-19. Our findings indicate that previous experience, existing professional communities, and wider networks were essential for practising and pre-service teachers to exercise agency. The study offers insights into the the development of individual and collective teacher agency, which can inform professional development to prepare teachers for future disruptions and educational challenges.